Interprofessional collaboration to manage allergic disorders in rural areas of Himachal Pradesh (Bangladesh Journal of Medical Science, 2022)
Background: Allergic disorders are common and affect a large population even in rural areas. Medical care is not easily accessible to rural population especially in hilly terrain. Health camps are effective method to deliver medical care in such areas. Interprofessional collaboration involving various professions who work together as a team for management of various disorders is being studied and practiced recently.Aims and Objectives: To study the impact of interprofessional collaboration at these rural health camps to control allergies prevalent in the rural areas of the region.Methodology: Around 18 interprofessional health camps involving doctors of various disciplines – ENT, pulmonary medicine, skin, eyes, yoga experts, health and sanitation workers, public health, lab technicians, pharmacist and nursing staff were held in rural areas with an attempt to manage allergic disorders prevalent there as a team. The treatment was provided as a collaboration of various professions.Results: 608 patients of allergic disorders were identified at these camps which were more prevalent in younger and middle age group and females. The common allergens were dust mite mix, pine mix, cockroach and grass pollen. Nasal allergies were more common followed by skin and pulmonary allergies. On follow up, allergies were more controlled (48%) in patients who followed interprofessional advise and treatment as compared to (5%) in those who didn’t follow the same.Conclusion: Allergic disorders can be best managed by a holistic approach of treatment involving various professions. Health camps through interprofessional approach are an excellent method to provide medical care to rural population in difficult hilly terrain.Bangladesh Journal of Medical Science Vol. 21(1) 2022 Page : 96-100